Contributions of nursing care in the prevention of skin lesions in newborns in the Neonatal Intensive Care Unit (Research, Society and Development, 2021)
To analyze the scientific evidence on nursing care in the prevention of skin lesions in newborns in the Neonatal Intensive Care Unit. The present study deals with a bibliographic review of the integrative literature review method, carried out between August and December 2020. The search was carried out, through the Platform - VHL, using the databases (LILACS), (BDENF), (MEDLINE), (IBECS), and through the Google Scholar Portal, adhering through the descriptors / keywords: “Newborn”, “Neonatal Intensive Care Units”, “Nursing Care”, “Cutaneous Development” , crossed with the Boolean operator “OR” and later combined with the Boolean operator “AND”. It is understood that the newborn's skin care is a broad process, which requires scientificity, responsibility, commitment, affection and dedication on the part of the nursing team. Thus, it is reinforced the statement that skin care “is a continuous, dynamic, effective, individualized, careful and humanized nursing intervention, aiming at the promotion, maintenance or recovery of the newborn's skin integrity , considering the physiological, environmental and assistance aspects ”. It is necessary to seek nursing care in the Neonatal Intensive Care Unit, due to its high complexity in care, to develop work methods related to newborn skin care, which provides a clear, unified nursing practice with short-term goals. and long term, favoring and explaining the effectiveness of the activities developed.